2016
DOI: 10.1021/acs.chemmater.6b00176
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Wurtzite Cu2SnS3 (CTS) Nanocrystals and Their Applications in Solar Cells

Abstract: In the development of low-cost, efficient, and environmentally friendly thin-film solar cells (TFSCs), the search continues for a suitable inorganic colloidal nanocrystal (NC) ink that can be easily used in scalable coating/printing processes. In this work, we first report on the colloidal synthesis of pure wurtzite (WZ) Cu2SnS3 (CTS) NCs using a polyol-mediated hot injection route, which is a nontoxic synthesis method. The synthesized material exhibits a random distribution of CTS nanoflakes with an average l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 55 publications
8
44
0
Order By: Relevance
“… 42 , 49 As the optical absorption plays a crucial role in determining the suitability of a material for photovoltaic and PEC application, we have recorded the optical absorption of CTS in the wavelength range of 300–1200 nm as shown in Figure 1 c and it is consistent with a recent report. 50 The optical band gap of the CTS NPs was calculated using the Tauc relation α hυ = B ( hυ – E g ) n , where B is the Tauc constant, h is Plank’s constant, υ is the photon frequency, and E g is the band gap of the material. In the Tauc plot shown in Figure 1 d, the band gap of CTS NPs is estimated at 1.1 eV, indicating that it can be effectively used as an absorber layer in a photoelectrochemical cell.…”
Section: Resultsmentioning
confidence: 99%
“… 42 , 49 As the optical absorption plays a crucial role in determining the suitability of a material for photovoltaic and PEC application, we have recorded the optical absorption of CTS in the wavelength range of 300–1200 nm as shown in Figure 1 c and it is consistent with a recent report. 50 The optical band gap of the CTS NPs was calculated using the Tauc relation α hυ = B ( hυ – E g ) n , where B is the Tauc constant, h is Plank’s constant, υ is the photon frequency, and E g is the band gap of the material. In the Tauc plot shown in Figure 1 d, the band gap of CTS NPs is estimated at 1.1 eV, indicating that it can be effectively used as an absorber layer in a photoelectrochemical cell.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed fabrication process of a full-device structure can be found in our previous reports. 37,38…”
Section: Methodsmentioning
confidence: 99%
“…But in the NIR region the collection efficiency is reduced, which indicates that the electronic properties (space charge region, carrier lifetime, and diffusion length) can be improved. [ 43–45 ] When the Se content increases in the absorber layer composition, the spectral range is increased from 900 (pure CZTS) to 1250 nm (pure CZTSe), remaining inside of this range those samples with partial S/Se substitution. It is also observed that the carrier collection is improved when the Cu content is increased.…”
Section: Resultsmentioning
confidence: 99%